2003
DOI: 10.1074/jbc.m212881200
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis Reveals Phosphorylation of ATP Synthase β-Subunit in Human Skeletal Muscle and Proteins with Potential Roles in Type 2 Diabetes

Abstract: Insulin resistance in skeletal muscle is a hallmark feature of type 2 diabetes. An increasing number of enzymes and metabolic pathways have been implicated in the development of insulin resistance. However, the primary cellular cause of insulin resistance remains uncertain. Proteome analysis can quantitate a large number of proteins and their post-translational modifications simultaneously and is a powerful tool to study polygenic diseases like type 2 diabetes. Using this approach on human skeletal muscle biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
160
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(180 citation statements)
references
References 50 publications
16
160
1
3
Order By: Relevance
“…Here, we demonstrate that human ATPsyn-β is phosphorylated at multiple specific sites in vivo. These results extend our previous work [21] and that of several other studies that have used various phospholabelling techniques or phosphopeptide identification by MS, which have provided indirect evidence for serine/ threonine/tyrosine phosphorylation of ATPsyn-β in yeast, plants and mammalian tissues and cell lines [27][28][29][30][31][32][33][34][35].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Here, we demonstrate that human ATPsyn-β is phosphorylated at multiple specific sites in vivo. These results extend our previous work [21] and that of several other studies that have used various phospholabelling techniques or phosphopeptide identification by MS, which have provided indirect evidence for serine/ threonine/tyrosine phosphorylation of ATPsyn-β in yeast, plants and mammalian tissues and cell lines [27][28][29][30][31][32][33][34][35].…”
Section: Discussionsupporting
confidence: 89%
“…However, although all sites were targeted in our analyses, of these we could only confirm the phosphorylation at Thr312 in human skeletal muscle. In addition to Thr213 [21] and Thr312 [27], we identified five novel phosphorylation sites at Thr475, Tyr230, Tyr269, Tyr361 and Tyr395, respectively. These data suggest the possibility that reversible phosphorylation of human ATPsyn-β at specific serine/threonine/tyrosine residues regulates the catalytic activity of ATP synthase, and hence ATP synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggest that HSP90 may serve to increase the amount of non-mutated relative to mutated insulin receptors. Interestingly, the level of HSP90 protein was recently reported to be increased in muscle of patients with type 2 diabetes [35]. Such an increase in HSP90 might antagonise the down-regulation of functional insulin receptors mediated by hyperinsulinaemia, and, as suggested by recent studies, preserve insulin signalling through Akt [36,37].…”
Section: Discussionmentioning
confidence: 97%
“…Recent investigations demonstrated that a number of the subunits of the respiratory chain enzyme complexes are phosphorylated, including several subunits of complex I. [45][46][47][48][49][50] As PINK1 protects cells against stress conditions that affect the mitochondrial membrane potential, which is maintained by the respiratory chain enzymes, it is tempting to speculate that PINK1 mediates its protective role through phosphorylation of certain respiratory chain enzyme subunits.…”
Section: Pink1 Mutationsmentioning
confidence: 99%